European forests are under increasing pressure from global change-driven invasions and accelerating epidemics by insects and diseases - Hartmann, Henrik; Battisti, Andrea; Brockerhof, Eckehard G.; Bełka, Marta; Hurling, Rainer; Jactel, Hervé; Oliva, Jonás; Rousselet, Jerome; Terhonen, Eeva; Ylioja, Tiina; Melin, Markus; Olson, Åke; et al. (Julius Kühn Institute (JKI), 2025)
Rising temperatures attributed to anthropogenic climate change have held a firm grip on European forests for over two decades now and disturbances have increased substantially, mainly from insects and pathogens. Empirical evidence suggests a direct linkage between rising temperatures and increasing damage from native insects. Although the rapid spread of non-native invasive pests and pathogens is mainly driven by globalized trade and lacking tree species adapta tion to locally new threats, climate change favors rapid range expansion of some invasive pests. Here, we present some examples of tree-insect-pathogen interactions in native and non-native systems that have experienced climate change-in duced severe outbreak dynamics. We document the spread of damaging insects and pathogens into previously climatically unsuitable regions and underscore the severe forest damages such species distribution shifts can cause. Although systematic assessments are still pending, the information provided here by multiple independent empirical evidences is highly valuable for identifying some of the most pressing issues in European forest protection. Our work can guide forest protection agencies in preparing mitigating strategies for upcoming decades.
Keywords: forest health; forest decline; forest protection; climate change